2006
DOI: 10.1038/sj.cdd.4401925
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of p53 stabilization and activation

Abstract: A number of proteins are activated by stress stimuli but none so spectacularly or with the degree of complexity as the tumour suppressor p53 (human p53 gene or protein). Once stabilized, p53 is responsible for the transcriptional activation of a series of proteins involved in cell cycle control, apoptosis and senescence. This protein is present at low levels in resting cells but after exposure to DNA-damaging agents and other stress stimuli it is stabilized and activated by a series of post-translational modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
550
3
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 612 publications
(581 citation statements)
references
References 93 publications
16
550
3
3
Order By: Relevance
“…We identified two serine residues, serine 15 and serine 33, that are remarkably phosphorylated by rpS3 knockdown (Figure 2b). These data lead to the speculation that the p38-dependent phosphorylation is involved in the p53 induction, since it has been demonstrated previously that the phosphorylation at these sites is regulated mainly by p38 kinase (Bulavin et al, 1999;Lavin and Gueven, 2006), and has an effect on the stability and activity of p53 (Bulavin et al, 1999;Kishi et al, 2001).…”
Section: Rps3-knockdown Exhibits Aberrant Ribosome Biogenesismentioning
confidence: 88%
“…We identified two serine residues, serine 15 and serine 33, that are remarkably phosphorylated by rpS3 knockdown (Figure 2b). These data lead to the speculation that the p38-dependent phosphorylation is involved in the p53 induction, since it has been demonstrated previously that the phosphorylation at these sites is regulated mainly by p38 kinase (Bulavin et al, 1999;Lavin and Gueven, 2006), and has an effect on the stability and activity of p53 (Bulavin et al, 1999;Kishi et al, 2001).…”
Section: Rps3-knockdown Exhibits Aberrant Ribosome Biogenesismentioning
confidence: 88%
“…Some of the modifications affect p53 localization and transcriptional activity, whereas certain modifications can direct p53 to a specific biological outcome, such as growth arrest versus apoptosis (reviewed by Meek, 2004;Lavin and Gueven, 2006). However, a fundamental requirement for p53 activation is the release of p53 from inhibition by the Mdm proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Most relevant to the relief from the Mdm proteins are the phosphorylation of Ser20, Thr18 and Ser15, which reside within the highly conserved hydrophobic loop that mediates p53 binding to the Mdm proteins. These phosphorylations protect p53 from inhibition by the Mdm proteins (Lavin and Gueven, 2006). Thr18 phosphorylation is considered the more critical of the two, as it directly attenuates its interaction with Mdm2 (Craig et al, 1999;Lai et al, 2000;Sakaguchi et al, 2000;Schon et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among kinase-dependent activity pathways acting on p53, only two are controlled by Ca 2 ĂŸ signaling. One of them involves serine/threonine kinase members included in a subgroup of the protein kinase C (PKC) family termed the classical group encompassing PKCs-a, -bI, -bII and -g. [24][25][26] The other one is facilitated by the ubiquitous Ca 2 ĂŸ -sensing protein CaM and occurs through activation of members contained in the superfamily of CaM-dependent kinases. [27][28][29] As a selective inhibitor of PKC (PKC412) did not attenuate p53 S15 phosphorylation in any of the concentrations tested, we concluded that this kinase did not contribute to the 5-FUinduced and Ca 2 ĂŸ -dependent events leading to p53 activity.…”
Section: Dr5mentioning
confidence: 99%